Hyalinizing clear cell carcinoma of the lung: a case report and literature review - Yu-Ju Su; Yun-Shao Wu; Cheng-Hung How; Min-Shu Hsieh (Diagnostic Pathology)
Abstract Background Primary pulmonary hyalinizing clear cell carcinoma (HCCC) is an exceedingly rare tumor with unique clinicopathological features, posing major diagnostic challenges. Case presentation We present a case of a 74-year-old woman with a lung nodule incidentally detected in the right middle lobe (RML) through 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) imaging. Through comprehensive evaluations by thoracic surgeons, she underwent video-assisted thoracic surgery of RML lobectomy to excise the lung nodule. Subsequent histopathological and immunohistochemical analyses confirmed the nodule as HCCC. She was discharged without any postoperative complications. No recurrence has been observed after two years of follow-up. This case underscored the importance of comprehensive imaging modalities and pathological analysis in the management of primary pulmonary HCCC. Conclusions This report highlights the critical role of imaging techniques and pathological analysis in diagnosing primary pulmonary HCCC, with this case demonstrating the essential value of 18F-FDG PET/CT integration.